2014
DOI: 10.1038/nn.3887
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of fibroblasts into peripheral sensory neurons

Abstract: Humans and mice detect pain, itch, temperature, pressure, stretch and limb position via signaling from peripheral sensory neurons. These neurons are divided into three functional classes (nociceptors/pruritoceptors, mechanoreceptors and proprioceptors) that are distinguished by their selective expression of TrkA, TrkB or TrkC receptors, respectively. We found that transiently coexpressing Brn3a with either Ngn1 or Ngn2 selectively reprogrammed human and mouse fibroblasts to acquire key properties of these thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
185
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(196 citation statements)
references
References 46 publications
9
185
1
1
Order By: Relevance
“…Previous work by the group that performed the current study showed that a pair of transcription factors from the basic helix-loophelix (bHLH) and Pit-Oct-Unc (POU) families can induce the expression of neuronal markers through direct reprogramming 6 . Tsunemoto et al were inspired by this finding in their current work.…”
Section: Ly N E T T E L I M and O S C A R M A R í Nmentioning
confidence: 93%
“…Previous work by the group that performed the current study showed that a pair of transcription factors from the basic helix-loophelix (bHLH) and Pit-Oct-Unc (POU) families can induce the expression of neuronal markers through direct reprogramming 6 . Tsunemoto et al were inspired by this finding in their current work.…”
Section: Ly N E T T E L I M and O S C A R M A R í Nmentioning
confidence: 93%
“…Indeed, this approach has been used for inducing many other neuronal subtypes lost in traumatic injury or neurodegenerative diseases, and generation of which in vitro could be potentially useful for cellbased therapies as well as for disease modelling (Blanchard et al, 2015;Caiazzo et al, 2011;Gascón et al, 2016;Rouaux and Arlotta, 2013;Son et al, 2011;Victor et al, 2014;Wainger et al, 2015). Especially for the latter, direct reprogramming has the advantage of maintaining the age of the starter cell (Mertens et al, 2015), in contrast to the re-setting that occurs when generating induced pluripotent stem cells (Lapasset et al, 2011).…”
Section: Neuronal Subtype Specification: From Dopaminergic Neurons Tomentioning
confidence: 99%
“…From a developmental perspective, these neurons differentiate from neural crest cells (Pavan and Raible, 2012), and hence a promising approach for generating them has been to reprogramme human fibroblasts into neural crest cells, which can then be further differentiated into peripheral neurons . However, direct neuronal reprogramming has proven to be more successful in obtaining specific subtypes of peripheral neurons than the neural crest cell route (Blanchard et al, 2015;Wainger et al, 2015). As peripheral sensory neurons are different to those of the central nervous system, an important question is how similar or different the molecular requirements are for inducing these cells.…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups recently reported exciting findings that suggest that mouse and human fibroblasts can be converted to iN cells with even such a high degree of subspecialization as the three main classes of peripheral sensory neurons, including nociceptive neurons that would be highly relevant for pain research [59,60]. The Baldwin group found that just two transcription factors, either Ngn1 or Ngn2, in combination with Brn3a, a critical lineage determination factor for peripheral neurons, was sufficient to convert both mouse primary and human iPS cell-derived fibroblasts to iN cells with peripheral identity representing the three major classes of sensory neurons: nociceptive, mechanosensitive and proprioceptive, which express the key specific markers TrkA, B and C, respectively [59]. The neurons exhibited a typical pseudounipolar morphology, expressed several additional markers of sensory neurons and responded to appropriate stimuli like capsaicin, menthol and mustard oil.…”
Section: (D) Generation Of Induced Peripheral Sensory Neuronsmentioning
confidence: 99%